Enhancing Critical Thinking Skills in Geography Education through Macromedia Flash and Image-Based Media - Yoga Puspa Sari; Wellfarina Hamer; Anita Lisdiana (Digital Learning, Social Science, and Life-course Studies, 2025)
This study investigates the impact of Macromedia Flash and image-based media on enhancing critical thinking skills among Grade 10 students in Geography at Senior High School 1 Seputih Mataram, Indonesia. A quasi-experimental design with pretest-posttest measures was used to compare two groups: an experimental group taught using Macromedia Flash and a control group taught with static image-based media. The assessment focused on five critical thinking dimensions: analysis, synthesis, problem-solving, evaluation, and inference. The results indicated significant improvements in the experimental group, particularly in analytical reasoning, problem-solving, and evaluation. Independent samples t-tests revealed that the Macromedia Flash group outperformed the image media group in all dimensions of critical thinking. These findings support the hypothesis that interactive multimedia fosters greater cognitive engagement and critical thinking, suggesting that Macromedia Flash is a valuable tool for promoting higher-order thinking in social science education. The study contributes to the growing body of literature on multimedia learning and underscores the potential of technology-integrated pedagogy in enhancing critical thinking at the secondary education level.